Variables associated with the performance of Centers for Dental Specialties in Brazil - Karine Laura Cortellazzi; Edna Cesar Balbino; Luciane Miranda Guerra; Fabiana de Lima Vazquez; Jaqueline Vilela Bulgareli; Glaucia Maria Bovi Ambrosano; Antonio Carlos Pereira; Fábio Luiz Mialhe (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
The aim of this study was to evaluate the performance of the Centers for Dental Specialties (CDS) in the country and associations with sociodemographic indicators of the municipalities, structural variables of services and primary health care organization in the years 2004-2009. The study used secondary data from procedures performed in the CDS to the specialties of periodontics, endodontics, surgery and primary care. Bivariate analysis by χ2 test was used to test the association between the dependent variable (performance of the CDS) with the independents. Then, Poisson regression analysis was performed. With regard to the overall achievement of targets, it was observed that the majority of CDS (69.25%) performance was considered poor/regular. The independent factors associated with poor/regular performance of CDS were: municipalities belonging to the Northeast, South and Southeast regions, with lower Human Development Index (HDI), lower population density, and reduced time to deployment. HDI and population density are important for the performance of the CDS in Brazil. Similarly, the peculiarities related to less populated areas as well as regional location and time of service implementation CDS should be taken into account in the planning of these services.